2015
DOI: 10.1130/ges01108.1
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami recurrence in the eastern Alaska-Aleutian arc: A Holocene stratigraphic record from Chirikof Island, Alaska

Abstract: Despite the role of the Alaska-Aleutian megathrust as the source of some of the largest earthquakes and tsunamis, the history of its pre-twentieth century tsunamis is largely unknown west of the rupture zone of the great (magnitude, M 9.2) 1964 earthquake. Stratigraphy in core transects at two boggy lowland sites on Chirikof Island's southwest coast preserves tsunami deposits dating from the postglacial to the twentieth century. In a 500-m-long basin 13-15 m above sea level and 400 m from the sea, 4 of 10 sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 131 publications
0
42
1
Order By: Relevance
“…(Nelson et al, 1996) and these additional ones (Alam et al, 2012;Atwater et al, 2005;Atwater et al, 2001;Bender et al, 2015;Carver and Plafker, 2008;Chagué-Goff et al, 2011;Dura et al, 2015;Dura et al, 2016;Dura et al, 2011;Engel and Brückner, 2011;Engelhart et al, 2013;Garrett et al, 2013;Goff et al, 2011a;Grand Pre et al, 2012;Kelsey et al, 2002;Martin and Bourgeois, 2012;McCalpin and Carver, 2009;Morton et al, 2007;Nelson et al, 2015;Nelson et al, 2006;Obermeier and Dickenson, 2000;Pilarczyk et al, 2014;Shennan, 2009;Shennan et al, 2014a;Shennan et al, 2014c;Walsh et al, 1995;Witter et al, 2003;Yamaguchi et al, 1997) parameters and deformation estimates from Nicolsky et al (2013, which Liquefaction Concurrent with Emergence Sand dikes and sills seen in outcrop or subsurface sampling using pits or a sediment slicer Sand dikes and sills seen in outcrop or subsurface sampling using pits or a sediment slicer In cores, difficult to differentiate from possible tsunami deposit Table Footnote: Inferences are made from evidence and comments are about evidence. Papers evaluated include those cited in the original version (Nelson et al, 1996) and these additional ones (Alam et al, 2012;Atwater et al, 2005;Atwater et al, 2001;Bender et al, 2015;Carver and Plafker, 2008;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Nelson et al, 1996) and these additional ones (Alam et al, 2012;Atwater et al, 2005;Atwater et al, 2001;Bender et al, 2015;Carver and Plafker, 2008;Chagué-Goff et al, 2011;Dura et al, 2015;Dura et al, 2016;Dura et al, 2011;Engel and Brückner, 2011;Engelhart et al, 2013;Garrett et al, 2013;Goff et al, 2011a;Grand Pre et al, 2012;Kelsey et al, 2002;Martin and Bourgeois, 2012;McCalpin and Carver, 2009;Morton et al, 2007;Nelson et al, 2015;Nelson et al, 2006;Obermeier and Dickenson, 2000;Pilarczyk et al, 2014;Shennan, 2009;Shennan et al, 2014a;Shennan et al, 2014c;Walsh et al, 1995;Witter et al, 2003;Yamaguchi et al, 1997) parameters and deformation estimates from Nicolsky et al (2013, which Liquefaction Concurrent with Emergence Sand dikes and sills seen in outcrop or subsurface sampling using pits or a sediment slicer Sand dikes and sills seen in outcrop or subsurface sampling using pits or a sediment slicer In cores, difficult to differentiate from possible tsunami deposit Table Footnote: Inferences are made from evidence and comments are about evidence. Papers evaluated include those cited in the original version (Nelson et al, 1996) and these additional ones (Alam et al, 2012;Atwater et al, 2005;Atwater et al, 2001;Bender et al, 2015;Carver and Plafker, 2008;…”
Section: Discussionmentioning
confidence: 99%
“…Newly applied analytical methods include stable carbon isotope and geochemical proxies Dura et al, 2011;Engelhart et al, 2013;Hawkes et al, 2011;Witter et al, 2016). The last decade has also seen a lot written on identifying sediments deposited by tsunami (Alam et al, 2012;Chagué-Goff et al, 2011;Dura et al, 2015;Engel and Brückner, 2011;Garrett et al, 2013;Goff et al, 2011a;Goff et al, 2011b;Goto et al, 2011;Grand Pre et al, 2012;Kortekaas and Dawson, 2007;Morton et al, 2007;Nelson et al, 2015;Okal et al, 2011;Pilarczyk et al, 2014;Shanmugam, 2012;Witter et al, 2016).…”
Section: Identifying Coseismic Subsidence and Uplift In Tidal-wetlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Paleotsunami research based on coastal geological records is a useful approach to the detection of high-magnitude, low-frequency tsunami events along subduction zones (e.g., Atwater 1987;Minoura et al 2001;Nanayama et al 2003;Cisternas et al 2005;Monecke et al 2008;Shishikura et al 2010;Ishimura and Miyauchi 2015;Nelson et al 2015;Kitamura 2016;Inoue et al 2017). Although previous paleotsunami research along the Ryukyu Trench has examined coralline boulders (herein, "tsunami boulders") (Kawana and Nakata 1994;Goto et al 2010;Araoka et al 2013), Ando et al (2018) recently identified three sandy tsunami deposits (T-I, T-II, and T-IV) and a layer of buried tsunami boulders (T-III) in a trench on Ishigaki Island (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent research has begun to address the paleo-tsunami record around the Pacific Ocean, with more studies needed (cf. Nelson et al, 2015).…”
Section: Quaternary Tectonic Framework and Seismic Hazardsmentioning
confidence: 99%